2020
DOI: 10.2217/fon-2020-0320
|View full text |Cite
|
Sign up to set email alerts
|

Afatinib for the First-Line Treatment of EGFR Mutation-Positive NSCLC in China: a Review of Clinical Data

Abstract: Mutations in the EGFR gene are particularly prevalent among Chinese patients with non-small-cell lung carcinoma. Six EGFR tyrosine kinase inhibitors are approved for the first-line treatment of EGFR mutation-positive non-small-cell lung carcinoma in China, which poses questions about which agent is most suitable for a particular patient. In this article, we review available clinical trial and real-world data with afatinib in Chinese patients. We assess its efficacy and safety in key patient subgroups such as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 83 publications
(143 reference statements)
1
2
0
Order By: Relevance
“…For T790M-negative patients, combination strategies involving targeted therapies hold the potential to overcome drug resistance. 24 Consistent with the published case report, the present study showed that one patient with EGFR uncommon mutation and MET amplification could obtain benefits from the combination of afatinib and crizotinib. 32 Our study suggested that afatinib plus anlotinib showed potent efficacy in one patient with EGFR G719X and FGFR1 amplification.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…For T790M-negative patients, combination strategies involving targeted therapies hold the potential to overcome drug resistance. 24 Consistent with the published case report, the present study showed that one patient with EGFR uncommon mutation and MET amplification could obtain benefits from the combination of afatinib and crizotinib. 32 Our study suggested that afatinib plus anlotinib showed potent efficacy in one patient with EGFR G719X and FGFR1 amplification.…”
Section: Discussionsupporting
confidence: 92%
“…Our results suggested that EGFR T790M (11%) and FGFR1 amplification (11%), MET amplification (11%), following by were CDK4 amplification (7%), PI3KCA activation (7%), RET fusions (4%), and BRAF mutations (4%) may be the main resistance mechanisms of afatinib in patients with EGFR G719X/L861Q/S768I. Meanwhile, given that afatinib was a type of pan‐ERBB inhibitor, ERBB2 amplification is less likely to be the major resistance mechanism 24 . Notably, the resistance mechanisms remained unclear in approximately 42% of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation